2022
DOI: 10.48550/arxiv.2204.03556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Goodbye Tracking? Impact of iOS App Tracking Transparency and Privacy Labels

Konrad Kollnig,
Anastasia Shuba,
Max Van Kleek
et al.

Abstract: Tracking is a highly privacy-invasive data collection practice that has been ubiquitous in mobile apps for many years due to its role in supporting advertising-based revenue models. In defence of user privacy, Apple introduced two significant changes with iOS 14: App Tracking Transparency (ATT), a mandatory opt-in system for enabling tracking on iOS, and Privacy Nutrition Labels, which disclose what kinds of data each app processes. So far, the impact of these changes on individual privacy and control has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…We also find that 42% of apps report that they do not collect any data from users. Recent works [29,30] analyzing iOS apps have found that at least 80% of the apps still use tracking libraries in the apps. Further, these libraries have been shown to collect user data [11,32].…”
Section: Apple Privacy Labelsmentioning
confidence: 99%
“…We also find that 42% of apps report that they do not collect any data from users. Recent works [29,30] analyzing iOS apps have found that at least 80% of the apps still use tracking libraries in the apps. Further, these libraries have been shown to collect user data [11,32].…”
Section: Apple Privacy Labelsmentioning
confidence: 99%